Ultrasmall Au and Ag Nanoclusters for Biomedical Applications: A Review - Tang, Jia; Shi, Haihong; Ma, Guanyu; Luo, Liangping; Tang, Zhenghua (Frontiers in Bioengineering and Biotechnology, 2020)
Noble metal (e.g., Au, Ag, Pt, Pd, and their alloys) nanoclusters (NCs) have emerged as a new type of functional nanomaterial in nanoscience and nanotechnology. Owing to their unique properties, such as their ultrasmall dimension, enhanced photoluminescence, low toxicity, and excellent biocompatibility, noble metal NCs—especially Au and Ag NCs—have found various applications in biomedical regimes. This review summarizes the recent advances made in employing ultrasmall Au and Ag NCs for biomedical applications, with particular emphasis on bioimaging and biosensing, anti-microbial applications, and tumor targeting and cancer treatment. Challenges, including the shared and specific challenges for Au and Ag NC toward biomedical applications, and future directions are briefly discussed at the end.